Polysulfide Confinement and Highly Efficient Conversion on Hierarchical Mesoporous Carbon Nanosheets for Li–S Batteries. Issue 42 (30th September 2019) - Li, Jianbo; Chen, Chunyuan; Chen, Yuwei; Li, Zhenhua; Xie, Wenfu; Zhang, Xin; Shao, Mingfei; Wei, Min
Abstract: Lithium–sulfur (Li–S) batteries have attracted increasing attention due to their extremely high theoretical specific capacity and a promising power density. However, practical applications of Li–S batteries are still limited by the relatively low performance, owing to poor conductivity of sulfur itself and discharge products (Li2 S/Li2 S2 ) as well as the shuttle effect of the intermediate polysulfide. Herein, honeycomb‐like mesoporous Co, N‐doped carbon nanosheets (MC‐NS) with a high specific surface area and abundant defects are developed which, simultaneously enable polysulfide confinement and highly efficient conversion. Moreover, density functional theory calculations and experiments show that the Co‐N‐C catalytic site as well as defects on the carbon skeleton of the MC‐NS facilitate high efficiency in suppressing the shuttle effect of polysulfides. In situ Raman spectra further demonstrate the enhancement of adsorption ability and conversion efficiency of polysulfides on this host. As a result, the MC‐NS enables much increased specific capacity and cycling stability of Li–S batteries. This work provides a useful strategy for realizing practical applications of high‐performance Li–S batteries. Abstract : A mesoporous carbon nanosheet (MC‐NS) is constructed through in situ growing ZIF‐67 on the surface of ZnAl‐LDH followed by a subsequent pyrolysis and acid etching. The obtained MC‐NS is demonstrated as an advanced sulfur carrier with simultaneously enhanced sulfur confinement and conversion efficiency which enables increased specific capacity and cycling stability, which is promising for future commercial Li–S batteries.